PETROGRAPHIC PROPERTIES OF PALAEOGENE SOUTHERN BANTEN COAL SEAMS WITH REGARD TO GEOLOGIC ASPECTS - BINARKO SANTOSO (Puslitbang tekMIRA, 2010)
The Palaeogene coal deposits occur in three coalfields in the Banten Province, which are distributed in Bayah, Cihideung and Cimandiri. The Bayah coals (Eocene Bayah Formation) mainly comprise vitrinite and subordinate inertinite and are of sub-bituminous A to high volatile bituminous A ranks (0.60-0.79%). The Cihideung coals (Eocene Bayah Formation) are of sub-bituminous A to medium volatile bituminous ranks (0.53-1.23%) and composed mainly of vitrinite. The Cimandiri coals (Oligocene Cijengkol Formation) are composed of variable proportions of vitrinite in the main and inertinite in very minor amounts. The rank of the coals is sub-bituminous A and high volatile bituminous A varying between 0.64% and 0.83% in vitrinite reflectance. Evaluation of these coals indicates that they tend to have similar coal petrographic properties and were formed in a littoral-neritic environment. Some of the coals, especially the Cihideung coals, show the highest vitrinite content and higher rank (0.99-1.23%), which is high A-medium volatile bituminous, due to an intrusive activity. Most of the coals have high contents of mineral matter (pyrite), mainly in the Bayah coals (2-13%), and this indicates that the coals were influenced by marine incursion during their deposition.